2020
DOI: 10.47093/2218-7332.2020.11.1.4-14
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of the concentration of sodium carboxymethylcellulose on hemostatic and antiadhesive activity during liver operations in an experiment

Abstract: Liver surgeries are associated with the risk of bleeding and the development of adhesive disease. Sodium carboxymethylcellulose (Na-CMC) forms an elastic swelling gel and a “lattice” that holds the blood cells.The aim: determine the concentration of Na-CMC, which has the maximum hemostatic and anti-adhesive effect, during liver surgeries in the experiment.Materials and methods. The coagulating effect of Na-CMC (from 0.5% to 9%) was studied in vitro. In vivo experiment on 167 male Wistar rats weighing 185–250 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Rats in the normal group did not receive Na-CMC. Soldatova et al (2020) reported that Na-CMC could affect hemostatic and provide an anti-adhesive effect in male Wistar rats at concentrations ranging from 3% to 6% 36 . To avoid things that are not expected in the normal control group, this group only receives standard pelleted rat feed and drink.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…Rats in the normal group did not receive Na-CMC. Soldatova et al (2020) reported that Na-CMC could affect hemostatic and provide an anti-adhesive effect in male Wistar rats at concentrations ranging from 3% to 6% 36 . To avoid things that are not expected in the normal control group, this group only receives standard pelleted rat feed and drink.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…Для это смешивали 0,05 г Nа-KМЦ, 0,05 г Пилим-1 и 4,90 мл воды. Na-КМЦ является оптимальным носителем для геля, так как ее растворы стойки к действию микроорганизмов, нетоксичны, физиологически инертны, устойчивы в широком интервале рН, хорошо всасываются, обладают высокой связывающей, диспергирующей, смачивающей и адгезивной способностью [7]. В качестве препарата сравнения использовали метилурацила мазь 10% для наружного применения (AO «Нижфарм», STADA, Россия).…”
Section: материалы и методы исследования металлокомплекс цинка под ла...unclassified
“…Для увеличения эффективности кровоостанавливающих средств производители добавляют в их состав различные лекарственные вещества (транексамовую кислоту, аминокапроновую кислоту и др. ), а также изделия подвергаются различным химическим и физическим воздействиям, меняющим их физико-химические свойства, например, уровень pH [7,8].…”
unclassified